Cholesteric Metronomes with Flexoelectrically Programmable Amplitude. Issue 12 (10th April 2018) - Joshi, Vinay; Chang, Kai‐Han; Varanytsia, Andrii; Paterson, Daniel A.; Storey, John M. D.; Imrie, Corrie T.; Chien, Liang‐Chy
Abstract: Replicating natural phenomena using soft material actuators is a major challenge for material scientists. For example, a metronome is a device that produces an audible beat at a selected interval. In anisotropic soft materials, a flexoelectrically‐driven cholesteric liquid crystal (CLC) can display a metronome‐like swinging effect when an applied electric field is normal to the helices of a CLC that are aligned normal to the substrates. The amplitude and direction of swing of a flexoelectrically‐driven CLC is electrically programmable. Combining a bimesogen and a CLC with an optimized helical pitch, the mixture enables a large flexoelastic ratio ( e / K = 2.758 CN ‐1 m ‐1 ) and swinging amplitude of 53°. Furthermore, assisted by polymer stabilization the composite mixture offers many benefits of electro‐optical characteristics including fast response time (425 µs) and high optical contrast (500:1) between the field‐on and field‐off states as well as wavelength‐independent transmittance. The advances in the flexoelectro‐optical behavior of cholesteric metronomes open new avenues for applications in information displays, sensors and photonic devices. Abstract : Cholesteric metronomes with flexoelectrically programmable amplitude are reported with a large tilt angle through polymer stabilized cholesteric liquid crystals doped with bimesogens. With in‐plane switching in a vertical standing helix, sub‐millisecond response time, low hysteresis, and wavelength‐independent electro‐optic characteristics are achieved.